New records of Ticapimpla Gauld, 1991 (Hymenoptera: Ichneumonidae: Pimplinae) from Brazil and French Guiana, with taxonomic notes - Diego G. Pádua; Ilari E. Sääksjärvi; Ricardo F. Monteiro; Marcio L. Oliveira (PENSOFT PUBLISHERS, 2022)
Background We report the genus Ticapimpla Gauld, 1991 from French Guiana and the species Ticapimpla amazonica Palacio et al., T. carinata Palacio et al., T. matamatae Palacio et al. and T. soinii Palacio et al. from Brazilian Amazonia. The new discoveries suggest that the genus is widely distributed in Amazonian lowland rain forests. In addition, we diagnose and illustrate the males of T. carinata and T. matamatae for the first time. Short diagnoses and layer-photos for all the Amazonian species are provided.
New informationThe genus Ticapimpla is reported for the first time from French Guiana and the species T. amazonica, T. carinata, T. matamatae and T. soinii from Brazilian Amazonia. In addition, the males of T. carinata and T. matamatae are diagnosed and illustrated for the first time.